Access to Sharia Financing for Micro Enterprises: Case Study of Micro Enterprises in Semarang, Indonesia - Mutoharoh, Mutoharoh; Kiryanto, Kiryanto (E-Jurnal Akuntansi; Vol 31 No 5 (2021), 2021)
Islamic banking by its principle is expected to play a dominant role compared to other funding providers to finance micro enterprises, which are the real industrial sector. This study aims to explain the perceptions of micro business actors based on their experience in accessing Islamic financing. This is a descriptive quantitative research that relies on the sample selected using purposive random sampling to obtain respondents who meet the criteria that support the research objectives. Primary data were collected through a structured questionnaire to owners and managers of micro-businesses in the Semarang and surrounding areas. A total of 184 data were obtained and processed with the help of statistical tools that is SPSS 22.0. Therefore, it is concluded that access to Islamic financing in terms of product, requirements, and services variables was quite good based on micro business actors’ view. Keywords: Access of Financing; Micro Enterprises; Islamic Bank.